CASE STUDY ON VIOLENCE AGAINST AHMADIYYA ADHERENTS IN INDONESIA IN THE REIGN OF PRESIDENT SUSILO BAMBANG YUDHOYONO - Agung Yudhistira Nugroho (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2017)
Ahmadiyya saga in Indonesia just like a never ending stories. Starting from the non-acceptance of them in society, violence and intimidation, pressure from Islamic organizations and the Indonesian Ulema Council. The government placed in the position of a dilemma. On one hand the government is required to protect its citizens in this regard Ahmadiyya followers are intimidated by a group or community that does not accept them, on the other hand the government must determine the manner in which the Government should disband and ban the Ahmadiyya. When the Ahmadiyya and other religious people defended using the excuse of the Universal Declaration of Human Rights, the UN Human Rights artificial precisely considered weak and unable to protect Palestinians from Israeli attacks.  From here then comes the problem of where the followers of the Ahmadiyya to be able to put themselves in a society that does not accept them, Not an easy task to find the right solution for this case. Solutions that can be offered is to address these differences by looking at the cornerstone of our country Pancasila which has a single slogan Unity in Diversity. In that case author also concern about how the the government in maintaining security for Ahmadiyya followers whom a citizen of Indonesia as well? This is what will be studied in this paper.